A palm game design as a development communication strategy to increase knowledge of sustainable oil palm for gen z and millennials in Jakarta - Sabrina, Stella; Sarwoprasodjo, Sarwititi; Hubeis, Musa; Azahari, Delima Hasri (Edelweiss Applied Science and Technology, 2024)
Oil Palm is often associated with environmental disasters, as its cultivation leads to the destruction of primary forests and contributes to climate change. Negative perceptions about oil palm have been increasingly amplified across social media platforms. Therefore, it is crucial to promote sustainable oil palm practices and counter these negative narratives through various channels, particularly digital media. This research focuses on creating a mobile game about oil palm, targeting the millennial and Gen Z communities. The game serves as an educational tool to address growing concerns in both Indonesian and international society regarding oil palm’s environmental and social impacts, including deforestation, biodiversity loss, social conflicts, and climate change. These issues are frequently discussed on platforms like Facebook, YouTube, and Twitter. By employing the ADDIE method, this research designed a game as part of a development communication strategy that blends education with entertainment. The goal is to raise awareness about sustainable oil palm practices among millennials and Gen Z in Jakarta.